Membangkitkan Gelora Wirausaha Muda dari Dunia Kampus - Andi Kasirang; Sulfiana Sulfiana; A. Susilawaty Hardiani; Andi Tenri Darhyati; Jamila Jamila (DEDIKASI, 2018)
The purpose of this activity is to arouse enthusiasm and shape the character of young entrepreneurs whoare independent, professional and characterized Aswaja, and so that prospective entrepreneurs can have access to theskills and knowledge to start and improve their business which will also have an impact on job creation. Themethods used are training, apprenticeship and guidance, mentoring, revolving fund assistance, business consultationand tenant supervision. The implementation of KDP activities includes: training consisting of 5 stages,entrepreneurship visits, entrepreneurship practices, provision of technology assistance, business consultation andimplementation of program sustainability. The results obtained are the development of tenant businesses, namelymushroom cultivation, tempe chips, taro chips, vegetable donuts and services. Besides that, the draft ofentrepreneurship textbooks, the results of published activities on online media. As well as establishing cooperationwith UKM Celebes Mushroom, Frame Insight Indonesia. In the second year, there are 5 independent entrepreneurs(tenants) based on science and professionalism for UIM students and graduates, and able to create jobs.